Fano factor evaluation of diamond detectors for alpha particles. Issue 10 (10th June 2016) - Shimaoka, Takehiro; Kaneko, Junichi H.; Sato, Yuki; Tsubota, Masakatsu; Shimmyo, Hiroaki; Chayahara, Akiyoshi; Watanabe, Hideyuki; Umezawa, Hitoshi; Mokuno, Yoshiaki
Abstract : This report is the first describing experimental evaluation of Fano factor for diamond detectors. High‐quality self‐standing chemical vapor deposited diamond samples were produced using lift‐off method. Alpha‐particle induced charge measurements were taken for three samples. A 13.1 ±0.07 eV of the average electron–hole pair creation energy and excellent energy resolution of approximately 0.3% were found for 5.486 MeV alpha particles from an 241 Am radioactive source. The best Fano factor for 5.486 MeV alpha particles, calculated from experimentally obtained epsilon values and the detector intrinsic energy resolution, was 0.382 ± 0.007.